Integrating emotional quality and apparent usability in the assessment of product desirability - Gosiaco, Katherine Grace T. (Animo Repository, 2008)
The study of affect and apparent usability experienced by consumers through product-user interaction is an emerging field in the design and development of products. Affect is found to be a significant factor that influences an individual's cognition and behavior. As such, consumers' decision making may be assessed as per the emotions evoked from the product rather than the traditional or conventional belief that decisions are based on the logic and rationalization of human beings. On the other hand, apparent usability is found to be a significant determinant of consumers' product preference on the perception that was is beautiful is in fact usable. This suggests that the perceived usability of a product represents as a criterion for consumers' purchasing decisions whereby products that are perceived to be usable are more likely bought. The considerable role of emotional quality and apparent usability in molding the perception of consumers towards a product compel for the integration of these dimensions in the conceptualization and evaluation of product designs. Emphasis is on the conceptualization stage of the design process as deemed appropriate for the context. As such, a methodology and a measurement system for the assessment of product designs considering the mediating effect of emotional quality and apparent usability in relation to product desirability is deemed necessary. The development of a Usability Perception and Emotion Enhancement Model contribute to the assessment of product designs. Emotional quality in the context of this study refers to the affective state engendered as influenced by product design attribute settings whereas apparent usability denotes the priori perceptions of consumers towards a product's aesthetic quality. In order to validate the developed model, application to a high involvement product, specifically through a mobile phone case study was conducted. Emotional quality is measured considering Richins' Consumer Emotion Set where Optimism, Love, and Discontent were obtained as the observable dimensions to measure such. On the other hand, apparent usability criteria were adopted from mobile phone usability questionnaire such that dimensions of Controllability, Attractiveness, and Ease of Use were deduced. Surveys were administered to mobile phone users to evaluate the product's design as per its emotional quality and apparent usability. Structural Equation Modeling (SEM) was utilized to analyze data collected as well as validate the model developed. As such, emotional quality and apparent usability were found to be mediating variables of product attributes and consumer rating of desirability. Results obtained revealed that mobile phone attributes related to dimensions such as area of the screen and length and width ratio of the body influences emotional quality whereas body shape and number button arrangement affects perceived usability. As these attributes induce emotions and influence one's perception of usability, it is essential that designers identify the effects of this attributes to the aforementioned dimensions such that knowledge gained can be utilized in the creation of more satisfying designs. The study of affect and apparent usability experienced by consumers through product-user interaction is an emerging field in the design and development of products. Affect is found to be a significant factor that influences an individual's cognition and behavior. AS such, consumers' decision making may be assessed as per the emotions evoked from the product rather than the traditional or conventional belief that decisions are based on the logic and rationalization of human beings. On the other hand, apparent usability is found to be a significant determinant of consumers' product preference on the perception that was is beautiful is in fact usable. This suggests that the perceived usability of a product represents as a criterion for consumers' purchasing decisions whereby products that are perceived to be usable are more likely bought. The considerable role of emotional quality and apparent usability in molding the perception of consumers towards a product campel for the integration of these dimension in the conceptualization stage of the design process as deemed appropriate for the context. As such, a methodology and a measurement system for the assessment of product designs considering the mediating effect of emotional quality and apparent usability in relation to product desirability is deemed necessary. The development of a Usability Perception and Emotion Enhancement Model contribute to the assessment of product designs. Emotional quality in the context of this study refers to the affective state engendered as influenced by product design attribute settings whereas apparent usability denotes the priori perceptions of consumers towards a product's aesthetic quality. In order to validate the developed model, application to a high involvement product, specifically through a mobile phone case study was conducted. Emotional quality is measured considering Richins' Consumer Emotion Set where Optimism, Love, and Discontent were obtained as the observable dimensions to measure such. On the other hand, apparent usability criteria were adopted from mobile phone usability questioonaire such that dimensions of Controllability, Attractiveness, and Ease of Use were deduced. Surveys were administered to mobile phone users to evaluate the product's design as per its emotional quality and apparent usability. Structural Equation Modeling (SEM) was utilized to analyze data collected as well as validate the model developed. As such, emotional quality and apparent usability were found to be mediating variables of product attributes and consumer rating of desirability. Results obtained revealed that mobile phone attributes related to dimensions such as area of the scree and length and width ratio of the body influences emotional quality whereas body shape and number button arrangement affects perceived usability. As these attributes induce emotions and influence one's perception of usability, it is essential that designers identify the effects of this attributes to the aforementioned dimensions such that knowledge gained can be utilized in the creation of more satisfying designs.